Diet dan nutrisi pasien gagal jantung: Tinjauan mini bagi praktisi klinis - Sidhi Laksono Purwowiyoto; Grace Trifena (ARGIPA (Arsip Gizi dan Pangan), 2021)
The incidence of Heart Failure (HF) continues to increase worldwide, but the prognosis remains poor. Nutrition is a lifestyle factor involved in the prevention of heart failure, unfortunately the effects of macro and micronutrients and dietary patterns in the development and treatment of heart failure are still minimal. This is reflected in the lack of nutritional recommendations in all HF clinical guidelines. This literature review uses 40 literature references in searching for diet and nutrition in heart failure patients. In this mini review, we will discuss the implications of diet for sodium restriction, calorie restriction, supplementation of fats, protein, and micronutrients in the management of HF. So it can be concluded that nutritional knowledge is needed for holistic management of heart failure patients starting from sodium restriction procedures, recommended diet, calorie restriction to supplementation.